Intellectual Property Rights Protection in Industry- University Collaboration to Increase Innovation and Promote Indonesia's Economic Competency - Ujang Suratno; Andy Sutrisno; Rahmanisa Purnamasari Faujura, (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
Collaboration between higher education institutions and industries plays a strategic role in enhancing innovation to support accelerated economic growth. This study discusses effective strategies to facilitate collaboration between the two parties through the protection of Intellectual Property Rights (IPR). Universities, as centers for research and development (R&D), can provide relevant knowledge and technology, while industries play a role in applying innovation results to the market. The relationship between universities and industries in Indonesia remains suboptimal, as each party tends to work with different priorities. This study employs a descriptive research specification with a qualitative approach. Primary data, consisting of survey results and interviews, serve as the main data for the research, supported by secondary data in the form of legal materials, including primary, secondary, and tertiary legal sources. The data are analyzed using a qualitative normative descriptive method. The protection of intellectual property rights (IPR) is a key element in driving investment in research and innovation while ensuring that economic benefits are distributed equitably. The proposed strategies include establishing collaborative policies, enhancing human resource capacity in IPR management, and developing an innovation ecosystem based on IPR. Through this approach, it is anticipated that collaboration between higher education institutions and industries will create significant added value for national economic growth.